Studi Fenomenologi Gaya Hidup Sehat dan Strategi Pencegahan Stunting di Wilayah Perdesaan - Handayani, Bekti; Moedjiherwati, Trijani (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
This study aims to understand the perception of rural communities in efforts to prevent stunting through a healthy lifestyle in rural areas. This is because the high prevalence of stunting in rural areas is also influenced by lifestyle, minimal access to nutrition, and low public understanding of public health. This study involved three subjects who were breastfeeding mothers living in rural areas of Serang Regency. This study used a phenomenological study approach with the Interpretative Phenomenological Analysis analysis method. Data were obtained through in-depth interviews and observations with categories based on statements from research subjects who carry out daily activities according to the character of the local rural community. The research subjects stated that the perception of rural communities in preventing stunting through a healthy lifestyle is still influenced by cultural factors, education levels, and limited access to health information. This study found that the majority of rural communities believe that strengthening a healthy lifestyle can help prevent stunting in rural areas. Various innovations are needed to strengthen education, socialization and understanding of village citizens regarding a healthy lifestyle in preventing stunting. This study also found that the role and involvement of community leaders also greatly contributed to building collective awareness of a healthy lifestyle for preventing stunting in rural areas.